Avaliação da ação antimicrobiana do ácido hipocloroso obtido a partir de dispositivo eletrolítico em canais radiculares infectados com enterococcus faecalis - Dallepiane, Felipe Gomes (2023)
The aim of the present study was to evaluate, in vitro, the antimicrobial action of hypochlorous acid in root canals infected against Enterococcus faecalis. Thirty extracted single-rooted human teeth were used for the present study. The coronal portion was sectioned at the cementoenamel junction, so that the remaining root has a length of 15 mm. Then, the samples were sterilized in an autoclave for 30 minutes at a temperature of 120°C. Then, the samples were inoculated with 100 μl of Enterococcus faecalis culture and immersed in microtubes containing 2 ml of BHI. The samples were kept immersed in bacterial culture for fourteen days and stored in a bacteriological oven at a temperature of 37°C, with renewal of the culture medium every 48 hours. After the contamination period, the samples were divided into three groups (n=10) according to the final irrigation protocol tested: G1: distilled water (control); G2: 2.5% sodium hypochlorite (2.5% NaOCl); G3: hypochlorous acid (Dentaqua). Colony forming units (CFUs) counts were performed to assess the decontamination effectiveness of the proposed treatments. Statistical analysis was performed using analysis of variance (ANOVA), followed by Tukey post-hoc (α=0.05). The substances tested were effective in reducing bacteria, when compared to the control group, with no statistical difference between them (p<0.05). Concluding that the hypochlorous acid produced by the Dentaqua device was effective in reducing bacteria.